Molecular Recognition of Rosmarinic Acid from Salvia sclareoides Extracts by Acetylcholinesterase: A New Binding Site Detected by NMR Spectroscopy. Issue 21 (27th March 2013) - Marcelo, Filipa; Dias, Catarina; Martins, Alice; Madeira, Paulo J.; Jorge, Tiago; Florêncio, M. Helena; Cañada, F. Javier; Cabrita, Eurico J.; Jiménez‐Barbero, Jesús; Rauter, Amélia P.
Abstract Acetylcholinesterase (AChE) inhibition is one of the most currently available therapies for the management of Alzheimer's disease (AD) symptoms. In this context, NMR spectroscopy binding studies were accomplished to explain the inhibition of AChE activity by Salvia sclareoides extracts. HPLC‐MS analyses of the acetone, butanol and water extracts eluted with methanol and acidified water showed that rosmarinic acid is present in all the studied samples and is a major constituent of butanol and water extracts. Moreover, luteolin 4′‐O‐glucoside, luteolin 3′, 7‐di‐O‐glucoside and luteolin 7‐O‐(6′′‐O‐acetylglucoside) were identified by MS2 and MS3 data acquired during the LC‐MSn runs. Quantification of rosmarinic acid by HPLC with diode‐array detection (DAD) showed that the butanol extract is the richest one in this component (134 μg mg−1 extract). Saturation transfer difference (STD) NMR spectroscopy binding experiments of S. sclareoides crude extracts in the presence of AChE in buffer solution determined rosmarinic acid as the only explicit binder for AChE. Furthermore, the binding epitope and the AChE‐bound conformation of rosmarinic acid were further elucidated by STD and transferred NOE effect (trNOESY) experiments. As a control, NMR spectroscopy binding experiments were also carried out with pure rosmarinic acid, thus confirming the specific interaction and inhibition of this compound against AChE. The binding site of AChE for rosmarinic acid was also investigated by STD‐based competition binding experiments using Donepezil, a drug currently used to treat AD, as a reference. These competition experiments demonstrated that rosmarinic acid does not compete with Donepezil for the same binding site. A 3D model of the molecular complex has been proposed. Therefore, the combination of the NMR spectroscopy based data with molecular modelling has permitted us to detect a new binding site in AChE, which could be used for future drug development.